Commercially Available Enteric Empty Hard Capsules, Production Technology and Application - Aleš Franc; David Vetchý; Nicole Fülöpová (MDPI AG, 2022)
Currently, there is a growing need to prepare small batches of enteric capsules for individual therapy or clinical evaluation since many acidic-sensitive substances should be protected from the stomach's acidic environment, including probiotics or fecal material, in the fecal microbiota transplantation (FMT) process. A suitable method seems to be the encapsulation of drugs or lyophilized alternatively frozen biological suspensions in commercial hard enteric capsules prepared by so-called Enteric Capsule Drug Delivery Technology (ECDDT). Manufacturers supply these types of capsules, made from pH-soluble polymers, in products such as AR Caps®, EnTRinsicTM, and Vcaps® Enteric, or capsules made of gelling polymers that release their content as the gel erodes over time when passing through the digestive tract. These include DRcaps®, EMBO CAPS® AP, BioVXR®, or ACGcaps™ HD. Although not all capsules in all formulations meet pharmaceutical requirements for delayed-release dosage forms in disintegration and dissolution tests, they usually find practical application. This literature review presents their composition and properties. Since ECDDT is a new technology, this article is based on a limited number of references.